In situ Transesterification of Biodiesel For Possible Biodiesel Production - Haitham Mohammed, Ali Al-Abee (2013)
The production of fatty acid methyl ester (FAME) by direct in situ alkaline-catalyzed transesterification of the triglycerides (TG) in castor seeds will be examined. The Reaction was conducted through in situ trasesterification processes using methanol and in associated with basic catalyst; calcium oxide. The reaction was studied to obtain the conditions where the product of biodiesel start forming, then obtained the effect of catalyst seed ratio to production rate. 10 g of grinded castor seed was mixed with methanol; 1:5 seed methanol mole ratio, and calcium oxide; in different percentage. The mixture was mixed for 4h under 60 oC. The effects of co-solvent; hexane, to the reaction is investigated as well. The product of biodiesel was quantified using GC, and characterized using GC & MC. Experimental results showed that the amount of castor oil was converted to biodiesel (FAME) started after mixing 4h under 60 oC, but it was in low yield compared to the total oil presented in the seed, and the conversion which obtained via in situ transesterification is lower than conversion which obtained via conventional transesterification in the present of the same conditions. In another hand, the present percentage of the catalyst has an effect to the conversion, whereby the conversion increase as the catalyst weight catalyst increase till it reach an equivalent with alcohol then start to decrease. Furthermore, the effects observed for the co-solvent; hexane and petroleum ether, were as purification of the product and had no effects towards product yield or conversion. In conclusion, the yield that obtained of biodiesel production from castor oil via in situ process is lower than that obtained via conventional process.